Krzemieniec - Ateny Wołyńskie = Wolyn Athens / [tekst i zdj.] Jan Skłodowski ; [tł. na jęz. ang. Magdalena Żmuda]. - Skłodowski, Jan (1950- ). ("Ad Oculos", 2006)
Album fotograficzny. Fotografie z lat 2004-2005.